Conflicts in a Closely Held Family Business: Durga and Company. Issue 1 (March 2018) - Joshi, Manoj; Dixit, Shailja; Sinha, Amit K.; Shukla, Balvinder
The purpose of this case is to investigate the nature of conflicts that arise in a closely held family business (CHFB) and to identify variables that ensure successful transition from one generation to the next. This case necessitates that in order to decide on the inheritance, a three-step process, prevention, management and resolution of conflict, is essential. It also highlights the gender bias in succession planning, ignoring the capabilities and competence of women in the family. Unstructured interviews around multiple stakeholders in the family business (FB) were taken identifying the core issues leading to conflicts. Triangulating with multiple sources or incumbents has reduced biases. It is observed that conflicts are inevitable within CHFBs. However, it is widely accepted that conflicts are paramount to forward progression both for the family and for the business, when it is constructive in nature. The case reflects the importance of understanding the critical issues around family and business. The outcome is useful in relaying better understanding on dimensions of conflicts that plague family-controlled business. Family businesses must relay importance of managing conflicts and bringing in earlier resolutions before they become extinct. The aftermath of not resolving such conflicts can be as catastrophic of destroying the FB and its wealth in the longer run.